Russkii mir . Russkii mir . Russian World . Русский мир - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Program devoted to two topics: Scottish people who came to Russia in the 17th and 18th centuries and then settled here; and Nikolai Naidionov, the prominent Russian entrepreneur and photographer. Contributors: Denisov, Aleksei (Anchor) Передача посвящена двум темам: шотландцам, обосновавшимся в России в XVII и XVIII веке, и выдающемуся русскому предпринимателю и фотографу Николаю Найдёнову. Создатели: Денисов, Алексей (Ведущий/Ведущая)